2005
DOI: 10.1128/jb.187.16.5658-5664.2005
|View full text |Cite
|
Sign up to set email alerts
|

Shigella dysenteriaeShuS Promotes Utilization of Heme as an Iron Source and Protects against Heme Toxicity

Abstract: Shigella dysenteriae serotype 1, a major cause of bacillary dysentery in humans, can use heme as a source of iron. Genes for the transport of heme into the bacterial cell have been identified, but little is known about proteins that control the fate of the heme molecule after it has entered the cell. The shuS gene is located within the heme transport locus, downstream of the heme receptor gene shuA. ShuS is a heme binding protein, but its role in heme utilization is poorly understood. In this work, we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
62
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 40 publications
9
62
0
Order By: Relevance
“…Despite the evidence that genes homologous to chuS have been shown to be up-regulated under iron-limiting conditions, that these homologues prevented heme toxicity in S. dysenteriae (7), and that no other heme-degrading enzyme has been identified in any E. coli strain, the precise role for ChuS and its homologues has been downplayed in recent reports to be that of a cytoplasmic trafficker of heme or a nonspecific oligomeric complex that binds to DNA (15,25). By carefully examining the spectral progression and CO measurement of ChuS-catalyzed degradation of heme in the presence of minimal amounts of ascorbic acid, we conclude that ChuS specifically degrades heme and suggest that His-193 is the essential amino acid responsible, similar to His-25 in HO-1 (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the evidence that genes homologous to chuS have been shown to be up-regulated under iron-limiting conditions, that these homologues prevented heme toxicity in S. dysenteriae (7), and that no other heme-degrading enzyme has been identified in any E. coli strain, the precise role for ChuS and its homologues has been downplayed in recent reports to be that of a cytoplasmic trafficker of heme or a nonspecific oligomeric complex that binds to DNA (15,25). By carefully examining the spectral progression and CO measurement of ChuS-catalyzed degradation of heme in the presence of minimal amounts of ascorbic acid, we conclude that ChuS specifically degrades heme and suggest that His-193 is the essential amino acid responsible, similar to His-25 in HO-1 (11).…”
Section: Discussionmentioning
confidence: 99%
“…A Shigella dysenteriae chromosomal knock-out of shuS, a homologue to chuS, was shown to be defective in utilizing heme as an iron source, and expression of ShuS was up-regulated when challenged with iron-limiting conditions (7). Furthermore, shuS was implicated to have a cytoprotective role against heme toxicity in that growth of the shuS knock-out mutant was impaired at intermediate concentrations of heme (15 M) and that shuS was absolutely required for colony growth at high heme concentrations (40 M) (7).…”
mentioning
confidence: 99%
“…Ischemia-reperfusion injury will also bring about significant intravascular hemolysis (31,32), again supplying substrate for HO. In these cases, the detoxifying effects of heme oxygenase include the clearance of heme, which in itself is cytotoxic (33)(34)(35). In contrast, it has been shown that heme oxygenase overexpression or induction can confer cytoprotection in the absence of aberrant, extracorpuscular hemoproteins (5, 13, 36 -38).…”
Section: Discussionmentioning
confidence: 99%
“…The BhuU and BhuV orthologues, HemU/HmuU and HemV/HmuV, form the permease and ATPase components, respectively, of the cytoplasmic membrane haem transporter. The Shigella BhuS orthologue, ShuS, has been suggested to act as a shuttle protein that potentiates the utilization or degradation of haem, depending upon the prevailing conditions (Wyckoff et al, 2005). Upstream of bhuR is the sequence 59-TTGAATN 17 TACAAT-39, which is similar to the consensus promoter sequence recognized by the major form of RNA polymerase.…”
Section: Identification Of Other Macrophage-induced Genes In B Pseudmentioning
confidence: 99%